Gender pedagogical practices in Moroccan schools: awareness, implementing, and attitudes - Ouabou, Said; Achraouaou, Hassan; Akhsay, Rachid; Outalb M’hand, Ahmed (Frontiers in Education, 2025)
IntroductionGender disparities and stereotypes persist in Moroccan schools, influenced by cultural, religious, and political factors. This study examines the integration of Gender Pedagogical Practices (GPPs) to address these issues and foster inclusive, equitable education.MethodsA mixed-methods study was conducted with 188 teacher trainees at the Teacher Training Center in Souss-Massa (Morocco). The data were collected through a survey on gender knowledge, implementation, and attitudes, classroom observations of 60 trainees, and an interview with a pedagogical actor.ResultsModerate awareness of gender concepts was observed, with no significant gender differences. Most trainees (68–91%) supported GPPs, such as equal opportunities and gender-collaborative environments, though (27–33%) struggled with mainstreaming gender into content or preventing inequalities. Observations showed effective gender-neutral practices but a focus on binary gender categories. The pedagogical actor highlighted practical adaptations despite low formal knowledge, with cultural resistance and resource limitations as barriers.DiscussionThe findings reveal a disconnect between awareness and practice, challenging the notion that knowledge drives GPP adoption. Cultural norms hinder awareness, yet practical efforts persist. Enhanced, culturally sensitive training and resources are needed to strengthen GPP integration, informing policies for equitable education in Morocco.